The association between heart failure and risk of fractures: Pool analysis comprising 260,410 participants - Liu, Xiao-peng; Jian, Xian-yu; Liang, Dong-liang; Wen, Jian-xiong; Wei, Yi-hong; Wu, Jian-di; Li, Yi-Qun (Frontiers in Cardiovascular Medicine, 2022)
Background HF and osteoporosis shared many common etiological risk factors. However, studies exploring whether patients with HF were associated with a higher risk of osteoporotic fracture resulted in inconsistent findings. This meta-analysis aimed to summarize the association between HF and the risk of incident fracture. Methods Following the Meta-analysis of Observational Studies in Epidemiology group recommendations, we searched multiple electronic databases (PubMed, Cochran Library, and EMBASE) for related studies from inception to April 30, 2021. Studies evaluating the risk of incident fracture in patients with HF compared with those without HF were included for analysis. The random-effects models were used to combine the estimated hazard ratios (HRs) of incident fracture associated with HF. Results We included 8 observational studies for meta-analysis. The sample size ranged from 5,613 to 87,748 participants, with a total of 260,410 participants included. The median follow-up duration was 5.0 years. Random-effects model analyses showed that compared with control groups, patients with HF were associated with a higher risk of all incident fractures (HR = 1.67, 95% CI = 1.30–2.16, P < 0.001) and hip fracture (HR = 2.20, 95% CI = 1.28–3.77, P < 0.001). The risk of all incident fractures was increased in all subgroup analyses according to age, sample size, sex, and follow-up duration. Conclusions Patients with HF were associated with a higher risk of incident fracture, as well as hip fracture.